1986
DOI: 10.1111/j.1432-1033.1986.tb09507.x
|View full text |Cite
|
Sign up to set email alerts
|

Covalent linking of poly(ethyleneglycol)‐bound NAD with Thermus thermophilus malate dehydrogenase

Abstract: Poly(ethyleneglyco1)-bound NAD (PEG-NAD) was covalently linked to Thermus thermophilus malate dehydrogendse with a bifunctional reagent, 3,3'-(1,6-dioxo-1,6-hexanediyl)bis-2-thiazolidinethione. The covalently linked malate-dehydrogenase -PEG -NAD complex (MDH-PEG-NAD) was purified by DEAE-Sephadex column chromatography to remove unbound PEG-NAD, and fractionated by blue-Sepharose column chromatography into four preparations: MDH-PEG-NAD I, MDH-PEG-NAD 11, MDH-PEG-NAD 111 and MDH-PEG-NAD IV. The average numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…One of the striking properties of dehydrogenase-NAD complexes is the intramolecular character of the reaction between the NAD moiety and the enzyme moiety, unlike the intermolecular reaction between free NAD and enzyme. Eguchi et al 97) and Nakamura et al 9s), converting L-malate or glucose in the presence of a chemical redox system for NAD recycling and monitoring the reaction, proved that the rate constants for malate dehydrogenase-PEG (M r 3,000)-NAD and glucose detrydrogenase-PEG (M r 3,000)-NAD complexes (spacer~ nm) were independent of the concentration of the complexes, showing first-order kinetics. In contrast, the reshlts of control experiments with free NAD and enzyme at a fixed ratio pointed to second-order kinetics.…”
Section: Water-soluble Enzyme --Coenzyme Conjugatesmentioning
confidence: 99%
“…One of the striking properties of dehydrogenase-NAD complexes is the intramolecular character of the reaction between the NAD moiety and the enzyme moiety, unlike the intermolecular reaction between free NAD and enzyme. Eguchi et al 97) and Nakamura et al 9s), converting L-malate or glucose in the presence of a chemical redox system for NAD recycling and monitoring the reaction, proved that the rate constants for malate dehydrogenase-PEG (M r 3,000)-NAD and glucose detrydrogenase-PEG (M r 3,000)-NAD complexes (spacer~ nm) were independent of the concentration of the complexes, showing first-order kinetics. In contrast, the reshlts of control experiments with free NAD and enzyme at a fixed ratio pointed to second-order kinetics.…”
Section: Water-soluble Enzyme --Coenzyme Conjugatesmentioning
confidence: 99%
“…The activity of the conjugate is still lower than that of the native enzyme and increases with the increase in the NAD' concentration, while the activity of the native enzyme at 68.8 mM NAD' is the same as that at 1.6 mM NAD'. This means that the conjugate has much larger apparent K, value for [8]. These larger K , values for exogenous NAD' of the conjugates are considered to be due to competitive inhibition by the bound NADH moiety.…”
Section: Characterization Of Ep+-ldh-nad 'mentioning
confidence: 99%
“…PEGylation, with the remarkable therapeutic and biotechnological potential of peptides and proteins, is a process of attaching polyethylene glycol (PEG) chains to molecules of interest . PEGylated NAD­(P) + derivatives have been developed for a long time to investigate cofactor regeneration for dehydrogenase-catalyzed reactions. , For example, NAD + -PEG has been reported to covalently bind to GDH or malate dehydrogenase and form enzyme-PEG-NAD + conjugates with dramatically accelerated reaction rates. Recently, Kim et al has demonstrated a boosted biohydrogen production rate using NAD + -conjugated dehydrogenases .…”
Section: Introductionmentioning
confidence: 99%
“…23 PEGylated NAD(P) + derivatives have been developed for a long time to investigate cofactor regeneration for dehydrogenase-catalyzed reactions. 24,25 NAD + -PEG has been reported to covalently bind to GDH 26 or malate dehydrogenase 27 and form enzyme-PEG-NAD + conjugates with dramatically accelerated reaction rates. Recently, Kim et al has demonstrated a boosted biohydrogen production rate using NAD + -conjugated dehydrogenases.…”
Section: ■ Introductionmentioning
confidence: 99%